Continuation of contraceptive use in BRAC villages: a life table analysis - Hadi, Abdullahel (BRAC Research and Evaluation Division (RED), 2019)
BRAC began its Family Planning Facilitation Program (FPFP) in December 1994 covering two districts (Nilphamari and Sherpur) although Moulavibazar and Habiganj districts were subsequently added in next year. The program aimed to improve the quality of life through an enhanced family planning initiative. While the increase in contraceptive prevalence in FPFP areas is reported significant, it was unclear whether such increase was real or an artifact of program data. Assessing the continuity of contraceptive use was considered an useful attempt to understand the quality and program sustainability. Keeping that in view, this study estimates the contraceptive continuation rate with differentials by social categories, and identifies major reasons of discontinuation in two districts where BRAC has family planning facilitation programs.